Pendidikan Dan Pelatihan Sebagai Upaya Peningkatan Kinerja Pegawai Perpustakaan - Azizah, Zsa Zsa Nur (Universitas Negeri Surabaya, 2019)
The purpose of this discussion is to solve problems at school. The problem in the school is the weak performance of library employees. This study uses a theory review from several reading sources. The technique of collecting data uses documentation that fits the theme of the article and interviews of the parties concerned. Based on the results of the study of theory and case studies found problems that arise in schools and there are impacts from these problems